Structural performance of dynamic message signs with adhesive and welded connections. (1st February 2022) - Seo, Junwon; Amatya, Ibin
Highlights: Ultimate strength testing was performed on two full-sized dynamic message sign (DMS). Strain, deflection, and load data along with inspection imagery were collected. Four different damage states were identified for the adhesive DMS. The welded DMS failed with weld and rupture failure modes. Abstract: This paper discusses the results from ultimate strength tests conducted on two full-sized dynamic message signs (DMSs) fabricated by a local producer located in South Dakota in the United States. Specifically, the ultimate strength testing was carried out on one DMS with adhesive joints and one with typical welded connections. For the ultimate testing, monotonic loadings were applied to each of the DMSs by a hydraulic actuator under the displacement-based control until failure. During each test, strain, deflection, and load data along with visual inspection imagery were collected to gain a better understanding of structural behaviors and failure modes of each of the individually tested DMSs. The ultimate strength testing revealed that four different damage states, including adhesive debonding initiation, propagation, excessive, and ultimate failure, were identified for the adhesive DMS of which the significant propagation of adhesive debonding was found to be utmost crucial damage state, whereas welded DMS failed with two failure modes (i.e., weld and rupture failure). The ultimate testing demonstrated that the adhesive DMS failed at 125 kN with the peak deflection of 96.14 mm, while the welded DMS failed at 146 kN with the peak deflection of 91.49 mm.